Approaching the evaluation and intervention of patients with Friedreich’s ataxia: A bibliographic review - Moreno Escobar, Silvia; Pérez Naranjo, Narcisa (Revista de Investigación en Logopedia, 2025)
Friedreich’s ataxia (FA) is an autosomal recessive hereditary neurodegenerative disease with cerebellar alterations. It causes motor difficulties that affect walking, speech and swallowing, together with neurological, behavioural and cognitive alterations as well as cardiac and sensory-perceptual symptoms. It requires multidisciplinary interventions that seem to show positive results in the evaluation scales of this ataxia and in its quality of life, although only physiotherapy has scientific evidence due to the significant degenerative motor deterioration that occurs in all cases. Other interventions, such as speech therapy, have not been as widely described, although their therapeutic need is recognized. The aim of the present literature review is to study which are the main cognitive, psycholinguistic and/or speech difficulties associated with the disease and to observe the described effects of speech therapy in FA, which rehabilitates alterations such as dysarthria, dysphagia and language disorders and its combination with other therapies in this disorder. The search is based on the PRISMA 2020 method, selecting 71 references after screening with inclusion and exclusion criteria. In conclusion, it is considered necessary to continue studying the associated characteristics, the evaluation and intervention techniques, as well as the effects and positive evidence of speech therapy in this ataxia since, as it is a disease considered "rare", the low incidence and the small size of the population samples studied make the study and generalization of results more complex.